Design Aspects Applied to Engineering: Technology Sustainable Development and Innovation in the Science Parks - Inglesis Barcellos, Ekaterina Emmanuil [UNESP]; Botura, Galdenoro [UNESP]; Paschoarelli, Luiz Carlos [UNESP]; Charytonowicz, J. (Springer, 2016)
Science Parks are sustainable environments where design, aligned with engineering, can achieve its maximum concept by linking scientific research and practical application. This action can facilitate implementation of new sustainable systems and methodologies in project areas as design process and design driven Innovation. The development of products focusing on R&D mixing engineering and design can produce conscious sustainable technological innovation. In Neo-Schumpeterian view, the development and evolutionary economics require constant innovation. Innovation creates new research-based frameworks applied in R&D. It allows the scientific production associated with scientific results, tested by design concepts and techniques and associated to engineering technical basis. The return of knowledge in a continuous systemic transfer system of science and practice in design promotes the improvement of the innovative technology in a more conscious way, which excels for verifying the theories and innovative ideas. in a more conscious contemporary lifetime.
Keywords: Design; Innovation; Technological parks; Sustainable technology